OP02 Women's Views on Smoking Cessation Services and National Tobacco Control Measures. (10th September 2013) - Barber, J; Rumsby, E; Parker, S; Mohebati, L; Venables, S; Lawson, K; Scanlon, T; Memon, A
Abstract : Background: A large proportion of public health resource is dedicated to smoking cessation services and national campaigns to control tobacco. Although it is well established that women start to smoke earlier, are more susceptible to smoking-related disease and find it harder to quit smoking than men, little research has been done to understand the perception of women regarding smoking cessation services and national tobacco control measures. Methods: Eleven women who had used the NHS Stop Smoking Service in East Sussex were engaged in focus group discussions. Data were subjected to manual and NVIVO software-based thematic analysis. Results: Women felt that tailoring of services to their needs would improve cessation rates. They expect the smoking cessation counsellors to be non-judgmental and to offer a psychological insight into addiction, however they shared differing opinions on the need for counsellors to be female or ex-smokers. They praised the continuity of care, capacity for peer support, flexibility of time and location and free cessation aids offered. Conversely, they felt the service was poorly advertised, that access was not universally good and that women would be more likely to access and engage with services if female-only groups and drop-in clinics were available. Use of social networking and integration of services into schools were highlighted as ways to engage young women. Opinion varied on the effect that removing cigarettes from view, limiting availability and increasing price would have on initiation and cessation. Campaigns focusing on appearance and consequences of passive smoke inhalation in children were praised, whilst most shock tactics were felt to be ineffective, with a more positive message being favoured. Discussion: Women value service flexibility in terms of group size, location and timing. Improved advertising, more universal access and more female-centred options such as female only groups may help to better meet women's needs. Women's suggestions of services, such as drop-in groups, which already exist is evidence that service promotion should be improved. Women are engaged by national campaigns focusing on appearance and effects of passive smoking on children; however more research is needed on whether positive messaging can have a greater impact on female cessation than shock tactics, and on how the effects of smoke on appearance can be made more relevant to younger women. More research is needed on the importance of counsellor characteristics, the effectiveness of group interventions, and whether social networking and support and accessing schools can alter smoking behaviour in younger women.